Camel Milk: Nutritional Composition and Potential Therapeutic Properties - Iqbal, Muhammad Naeem; Ashraf, Asfa (PSM Biological Research, 2023)
Camel milk has an important role in food security and rural economy. Camel milk has superior nutritional quality and purported medicinal properties against a range of human illnesses. In this issue, Dogondaji et al. (2023) analyzed the proximate composition of the camel milk samples and reported average nutrient quality content. The claimed therapeutic property of camel milk is attributed to its possession of various bioactive compounds. The importance of camel milk in human nutrition and its potential health benefits lies in the fact that it is very similar to human milk. It is an excellent source of well-balanced nutrients and also exhibits a range of biological activities. Further studies must be planned for knowing the role of camel milk in handling many common diseases.